Acrylic Acid‐Allylpolyethoxy Carboxylate Copolymer as an Effective Inhibitor for Calcium Phosphate and Iron(III) Scales in Cooling Water Systems. Issue 7 (15th May 2015) - Liu, Guangqing; Zhou, Yuming; Huang, Jingyi; Yao, Qingzhao; Ling, Lei; Zhang, Peixin; Fu, Change; Wu, Wendao; Sun, Wei; Hu, Zhengjun
<x xml:space="preserve">Abstract</x> A novel type of calcium phosphate and iron(III) scale inhibitor acrylic acid‐allylpolyethoxy carboxylate AA‐APELn (ALn) was synthesized. The observation shows that the adsorption of the ALn copolymer on the crystal surface caused deformation of calcium phosphate crystal morphology. Furthermore, both calcium phosphate and iron(III) inhibition increase with increasing the degree of polymerization of ALn from 5 to 15, and the dosage of ALn plays an important role on calcium phosphate and iron(III) inhibition. Inhibition mechanism is proposed that the interactions between calcium or iron ions and polyethylene glycol (PEG) are the fundamental impetus to restrain the formation of the scale in cooling water systems.